Food a multicultural feast - Schrank, Jeffrey; Learning Seed ([S.l.]: Learning Seed, 1998)
Examines the multi-cultural origins of many foods and unearths a few surprises. They also learn that food serves as a common bond between peoples
Keywords: Food habits -- Cross-cultural studies; Food; Multiculturalism; Cookery, International; Home economics